Audit Committee Accounting Expert and Earnings Management with "Status" Audit Committee as Moderating Variable - Edy Suprianto; Suwarno Suwarno; Henny Murtini; Rahmawati Rahmawati; Dyah Sawitri (Indonesian Journal of Sustainability Accounting and Management, 2017)
This research aims to analyze the effect of accounting expert of audit committee on earnings management. This research also assesses the role of audit committee on earnings management with audit committee status as moderating variable. The population is all of firm's which listed in Indonesia Stock Exchange. Purposive sampling is used to collect data. Data used financial statements and annual report companies from Indonesia Stock Exchange website. Moderated regression analysis (MRA) is used to analyze the hypothesis. The result shows that accounting expert of audit committee has negative effect on earnings management. Yet, variable of audit committee status cannot moderate the relationship between accounting expert of audit committee and earnings management in Indonesia.